TI_GERICHTE 12.2012.108 vom 5. Februar 2014 , Contratto di assicurazione - assicurazione infortuni - prescrizione - nesso naturale - TI Tribunale d'appello (2014)
Contratto di assicurazione - assicurazione infortuni - prescrizione - nesso naturale